2010
DOI: 10.1161/circep.109.928820
|View full text |Cite
|
Sign up to set email alerts
|

Contactin-2 Expression in the Cardiac Purkinje Fiber Network

Abstract: Background-Purkinje cells (PCs) comprise the most distal component of the cardiac conduction system, and their unique electrophysiological properties and the anatomic complexity of the Purkinje fiber network may account for the prominent role these cells play in the genesis of various arrhythmic syndromes. Methods and Results-Differential transcriptional profiling of murine Purkinje fibers and working ventricular myocytes was performed to identify novel genes expressed in PCs. The most highly enriched transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
129
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(142 citation statements)
references
References 48 publications
9
129
0
4
Order By: Relevance
“…Cx40 is the best characterized and most specific known marker for VCS cells; it is not expressed by the AVN or the ventricular working myocardium. Other specific and useful VCS markers that have been identified in mice are Irx3 (Christoffels et al, 2000;Zhang et al, 2011), Hcn4 (after birth; Liang et al, 2013), CCS-lacZ (Rentschler et al, 2001) and Cntn2-EGFP (Pallante et al, 2010). Furthermore, Tbx3 is selectively expressed in the AVB and BB, but not in the Purkinje fibre network (Hoogaars et al, 2004).…”
Section: Development Of the Ventricular Conduction Systemmentioning
confidence: 99%
“…Cx40 is the best characterized and most specific known marker for VCS cells; it is not expressed by the AVN or the ventricular working myocardium. Other specific and useful VCS markers that have been identified in mice are Irx3 (Christoffels et al, 2000;Zhang et al, 2011), Hcn4 (after birth; Liang et al, 2013), CCS-lacZ (Rentschler et al, 2001) and Cntn2-EGFP (Pallante et al, 2010). Furthermore, Tbx3 is selectively expressed in the AVB and BB, but not in the Purkinje fibre network (Hoogaars et al, 2004).…”
Section: Development Of the Ventricular Conduction Systemmentioning
confidence: 99%
“…and xylaxine (10 mg per kg body weight i.p.). Excised hearts were fixed overnight in 4% paraformaldehyde and cryosections prepared and stained as previously described (13). Immunostaining of cryosections from cadaveric fetal human tissues fixed in 10% neutral buffered formalin was performed.…”
Section: +mentioning
confidence: 99%
“…The mechanisms responsible for this proarrhythmic propensity are incompletely understood, but compared with working ventricular myocytes (VMs), differences in T-tubular density (7), relative abundance of L and T type calcium channels (8), presence of IP 3 -sensitive Ca 2+ channels (9), greater intracellular sodium load (10), and the differential density of various repolarizing currents (11), are all considered contributory factors underlying the unique action potential (AP) and calcium-handling characteristics of PCs (12,13). Triggered mechanisms have been proposed to underlie PC-related ventricular arrhythmias, and PCs have been found to be more susceptible to both early afterdepolarizations (EADs) and delayed afterdepolarizations (DADs) compared with working VMs (5,14).…”
Section: Introductionmentioning
confidence: 99%
“…We found that expression of Cx40 and Na v 1.5 was drastically reduced in the VCS after removal of Tbx5 ( Figure 5). The proximal AV bundle and distal AV bundle/bundle branches were identified by their anatomic location, acetylcholinesterase activity (12,(17)(18)(19), and contactin-2 expression (20). Tbx5 fl/fl controls demonstrated high Cx40 and Na v 1.5 expression throughout the molecularly defined VCS, whereas Tbx5 minKCreERT2 animals demonstrated dramatic Values are mean ± SD.…”
Section: Figurementioning
confidence: 99%